Group learning activities as a condition of implementing competence-based approach to students’ inorganic chemistry teaching at university - Yaroshenko, О.G.; Blazhko, O.A.; Korshevniuk, T.V.; Blazhko, A.V. (KSU Publ., 2020)
The article presents the results of experimental testing the effectiveness of group learning activities of students at Inorganic Chemistry laboratory classes. The future teachers had their classes according to a technique based on research paper analysis findings with due account for practice of implementing the concept of group educational activity of senior pupils in Ukraine. The following issues were briefly addressed: special aspects of activities performed by group learning individuals; educational result of inorganic chemistry students presented in the form of general and special (occupational and subject) competences; preparation and order of laboratory classes for small groups of students as subjects. The order, course and results of the pedagogical experiment are presented. The results suggest that using the students' group learning activities is an effective tool for implementation of the competence-based approach to inorganic chemistry educational process, which contributes to lining-up the order and course of inorganic chemistry laboratory practicals. We wish to make a point that using group learning for actualization of the competence-based approach to learning chemistry of students requires certain methodological training of the faculty.
Топтық оқу іс-әрекеті университет студенттеріне бейорганикалық химияны оқытуда құзыреттілік тәсілді іске асырудың шарты ретінде
Групповая учебная деятельность как условие реализации компетентностного подхода в обучении неорганической химии студентов университета
Keywords: competency-based approach; the Inorganic Chemistry academic discipline; group learning activity; group learning technique; group learning individual; students; academic staff; laboratory practicals